An overview on understanding the major bacterial fish diseases in freshwater salmonids - Ahmed, Imtiaz; Ishtiyaq, Shagufta; Sayed, Shabihul Fatma (Frontiers in Aquaculture, 2025)
Exhaustive work on bacterial fish diseases provides a significant knowledge about the influence of bacterial infections in economically noteworthy freshwater fish species farmed around the world. However, it is still difficult to exactly pinpoint the causes of bacterial infections among wide diversity of fish species, although significant strides in this direction have been achieved with respect to different fish species. Various studies have demonstrated the growing prevalence of bacterial infections, concurrent with the rapid development of aquaculture worldwide, yet information regarding these infections, their influence on the host species, consequences of numerous environmental variables as well as social-economic impacts are still lacking, which warrant for a desperate need of detailed studies. Despite various efforts, the pathogenesis, appropriate diagnostic techniques and treatment measures of various diseases remains unclear and thus responsible for huge losses both in natural as well as aquaculture conditions. In addition, progress in control and prevention of these diseases is hampered by the lack of adequate epidemiological data on bacterial diseases in many countries. In the present review, an attempt has been made to bring together the scattered information available about the diverse features of most economically significant bacterial diseases affecting fresh water salmonids worldwide including: bacterial gill disease, columnaris disease, bacterial kidney disease, enteric red mouth disease, lactococcosis, furunculosis, bacterial coldwater disease, mycobacteriosis and photobacteriosis. Besides, we also tried to highlight a brief overview of the traditional techniques for isolating bacteria from their hosts along with the serological and/or genetic diagnostic tools. The development of immunisation techniques to stop certain bacterial infections is also discussed in this review paper. The study focuses on the latest fundamental knowledge linked to bacterial infections in freshwater systems covering epidemiology, clinical signs/pathogenesis, transmission, diagnosis and treatment measures while the pathogenesis data emphasizes the area calling for further investigation.